Christian Ideals in British Culture - Nash, D. author. aut Link
IX, 257 p.
Keywords: This book offers a challenge to conventional histories of secularisation by focusing upon the importance of central religious narratives. These narratives are changed significantly over time, but also to have been invested with importance and meaning by religious individuals and organisations as well as by secular ones.